A comparison between the effects of low (1 ?g) and standard dose (250 ?g) ACTH stimulation tests on adrenal cortex functions with Behcet's disease - Colak, R.; Ozkan, Y.; Cengiz, S. U.; Saral, Y.; Kandi, B. C.; Halifeoglu, I. (Wiley, 2006)
Introduction Behcet's disease is a rare, chronic disorder. The cause of Behcet's disease is unknown. It is believed to be caused by an autoimmune reaction. As in other chronic autoimmune diseases, Behcet's disease may show a subclinical adrenal failure and some changes in cortisol levels. We aimed to evaluate adrenal gland function in Behcet's disease patients. Material and method This study included 18 Behcet's disease patients and 15 healthy controls. Patient and control groups were administered i.v. 1 mu g low dose test (LDT) and 250 mu g standard dose test (SDT) adrenocorticotropic hormone (ACTH) stimulation test after 12 h of night fasting with an interval of 3-days and cortisol responses in the 0th, 30th and 60th minutes were evaluated. Results There was no statistically significant difference between basal cortisol values of Behcet's disease and control groups. Cortisol values in the 60th minute in LDT were significantly lower in Behcet's disease group than in the control group. In the peak cortisol responses to LDT, a significant decrease was found in Behcet's disease group. Conclusion These findings suggest that hypothalamo-pituitary adrenal axis is partially suppressed in Behcet's disease.
Keywords: ACTH stimulation test; Behcet's disease; subclinical adrenal failure